A Comparative Analysis of Microstrip Patch Antenna for Mics and Ism Frequency Antennas Applied to Wban - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper presents a comparative analysis of Microstrip Patch for MICS frequency bands of 403 MHz, 2.36 GHz and ISM band frequency of 2.4 GHz; and UWB band of 5.7 GHz under the norm IEEE 802.15.6. Regarding the design of the antennas, it is considered the Substrate Dielectric (FR4) with permittivity of 4.7, loss tangent of 0.019 and substrate s height of 1.6 mm. The results were obtained by Computer Simulation Technology (CST) software in terms of return loss, gain, Voltage Standing Wave Ratio (VSWR) and, radiation pattern. © 2015 IEEE.